Digital Literacy In The Class Room As Blended Learning: A Way Out To Promote Students In Learning - Ana Setyandari (Journal of Innovative and Creativity, 2022)
This paper offers an over views of blended learning and digital litracy. Since COVID-19 pandemic has spread out the world, it created a global rapid changes in every aspect of life, including in teaching and learning. Schools during the pandemic force us to create a new method in their teaching and learning activity system, namely the online system, where the implementation of learning activities was carried out using technological media such as mobile phones, computers or laptops. Blended learning in education becomes more popular in recent years with the help of technology. How do the students will find it effectively in solving the problem while using the digital literacy?. Here the researchers make recommendation of using digital literacy in the classroom.